2016
DOI: 10.1080/14656566.2016.1217994
|View full text |Cite|
|
Sign up to set email alerts
|

Baseline characteristics and interim (3-month) efficacy and safety data from STELLA-LONG TERM, a long-term post-marketing surveillance study of ipragliflozin in Japanese patients with type 2 diabetes in real-world clinical practice

Abstract: These 3-month interim results indicate that ipragliflozin improved glycemic control, lipids, and blood pressure with low rates of ADRs in Japanese patients with type 2 diabetes in real-world clinical practice. The results were consistent with those of placebo-controlled, randomized clinical trials. Clinicaltrials.gov identifier: NCT02479399.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 34 publications
4
34
1
5
Order By: Relevance
“…The safety and efficacy of ipragliflozin in type 2 diabetes patients has been shown through clinical trials and post‐marketing surveys. Several studies have shown that ipragliflozin lowers blood glucose levels in an insulin‐independent fashion, and hence is expected to be efficacious in type 1 diabetes, as well as type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The safety and efficacy of ipragliflozin in type 2 diabetes patients has been shown through clinical trials and post‐marketing surveys. Several studies have shown that ipragliflozin lowers blood glucose levels in an insulin‐independent fashion, and hence is expected to be efficacious in type 1 diabetes, as well as type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The initial report describes in detail the way in which the minimum sample size was calculated and the rationale for the duration of the study. Of note, no sample size calculation was considered regarding the subgroup comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…The study is currently ongoing; patients will be observed for a total of 3 years. The baseline characteristics of the patients have been reported previously; notably, the proportion of overweight or obese patients registered for the study is unexpectedly large compared with the general Japanese population. Here, we describe a subgroup analysis of the 3‐month interim results from STELLA‐LONG TERM, in which patients were stratified by BMI to investigate the impact of obesity on the efficacy and safety of ipragliflozin.…”
Section: Introductionmentioning
confidence: 93%
“…4 The regular dose of ipragliflozin is 50 mg/day and doses up to 100 mg/day are approved in cases of insufficient efficacy. [7][8][9][10] Furthermore, in a multicentre, randomized, placebo-controlled, double-blind study in insulin-treated patients with type 2 diabetes mellitus, ipragliflozin was shown to be well tolerated and effective. 5,6 The safety and efficacy of ipragliflozin in type 2 diabetes mellitus patients (including elderly patients) have been confirmed in preapproval clinical trials, as well as in large-scale postmarketing surveillance studies in the realworld clinical setting in Japan.…”
mentioning
confidence: 99%
“…5,6 The safety and efficacy of ipragliflozin in type 2 diabetes mellitus patients (including elderly patients) have been confirmed in preapproval clinical trials, as well as in large-scale postmarketing surveillance studies in the realworld clinical setting in Japan. [7][8][9][10] Furthermore, in a multicentre, randomized, placebo-controlled, double-blind study in insulin-treated patients with type 2 diabetes mellitus, ipragliflozin was shown to be well tolerated and effective. 11 Although there is a large amount of published data on the efficacy and safety of ipragliflozin for type 2 diabetes, to date, no data have been obtained on the use of ipragliflozin for the treatment of type 1 diabetes mellitus.…”
mentioning
confidence: 99%